Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/anie.200990033
|View full text |Cite
|
Sign up to set email alerts
|

Cover Picture: Solid‐State Scrolls from Hierarchical Self‐Assembly of T‐Shaped Rod–Coil Molecules (Angew. Chem. Int. Ed. 9/2009)

Abstract: Solid scrolls are reversibly formed by self‐assembly of rod‐shaped molecules with laterally attached coil units, in contrast to the layered structures formed from self‐assembly of planar molecules. As described by M. Lee and co‐workers in their Communication on the core structure of the scrolls, which are either filled cylinders or hollow tubes, can be controlled by variation of the length of the coil unit. The cover picture shows aligned tubular scrolls displaying well‐defined in‐plane ordering of the rod se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 0 publications
1
35
0
Order By: Relevance
“…Under similar conditions, the coupling reactions of 4-methoxybromobenzene also underwent with 88% yield (entries 5). However, the coupling reactions of 4-methylbromobenzenes underwent only in 10% yield (entries 6) and no reaction took place in bromobenzenes including electron-deficient substrates (entries 7,8), it showed that the more electrons on the benzene ring the more liable coupling reactions will happen. The crosscoupling reaction of aryl chloride including electron-rich and electron-deficient substrates didn't take place because which is generally unreactive under the conditions employed to couple aryl bromides and aryl iodides (entries 9-11).…”
Section: Self-organization Of Amphiphilic Diblock Rod-coil Moleculementioning
confidence: 94%
See 1 more Smart Citation
“…Under similar conditions, the coupling reactions of 4-methoxybromobenzene also underwent with 88% yield (entries 5). However, the coupling reactions of 4-methylbromobenzenes underwent only in 10% yield (entries 6) and no reaction took place in bromobenzenes including electron-deficient substrates (entries 7,8), it showed that the more electrons on the benzene ring the more liable coupling reactions will happen. The crosscoupling reaction of aryl chloride including electron-rich and electron-deficient substrates didn't take place because which is generally unreactive under the conditions employed to couple aryl bromides and aryl iodides (entries 9-11).…”
Section: Self-organization Of Amphiphilic Diblock Rod-coil Moleculementioning
confidence: 94%
“…[1][2][3][4][5][6] An example of a self-assembling system is provided by rod-coil molecules, which have a strong tendency to self-organize into a variety of supramolecular structures in nano-scale dimensions. [7][8][9][10][11][12] Amphiphilic rod-coil molecules are of great interest for nano-functional materials due to its intrinsic self organization property at the aqueous solution and used as suitable biomembrane and supra-nanoreactor system. [13][14][15][16][17][18][19] Lee and Jin have previously synthesized an amphiphilic coil-rod-coil molecule that contains polymerizable vinyl groups in the middle of the rod segment, which self-organizes into 2-D columnar structure and transfers to cross-linking nano-fiber via photopolymerization at the liquid crystalline state.…”
Section: Introductionmentioning
confidence: 99%
“…[10] When aromatic segments based on an imidazole unit self-assemble into a single layer, for example, the hydrogen bonding asymmetry between up and down planar surfaces drives the planar structure to roll up into scrolls owing to different surface tension. [11] Along with surface anisotropy, self-folding can be achieved by packing changes in aromatic crystals. For example, the aromatic macrocycle dimers based on anthracene units self-assemble into highly curved structures driven by molecular sliding of anthracene stacks.…”
Section: Static and Dynamic Nanosheets From Selective Assembly Of Geomentioning
confidence: 99%
“…Pd(PPh 3 ) 4 [19], benzothiadiazole (1) [20] (13) [26] were synthesized according to the literature procedures.…”
Section: Synthesis Of Monomers and Polymersmentioning
confidence: 99%